Diversifying Chili Products and Managing Business For Harvest Season Solutions : International Collaboration for Community Service - Setiyoko, Agus; Wulandari, Ika; Tokiman, Nurul Azlin (Jurnal Pengabdian UNDIKMA, 2025)
This community service program aims to enhance farmers' understanding and skills about various processed chili products, labeling and packaging technologies, and financial management. The program's approach is conseling, incorporating theories related to the diversification of processed chili commodities, branding, and packaging types alongside financial management procedures. The training progressed with the production of chili-based commodities, including chili syrup, chili candy, chili blocks, and chili chips. Training on labeling and packing, in addition to financial management techniques. The evaluation instrument used was a pre-test and post-test questionnaire to assess changes in participants’ knowledge. The data were analyzed using descriptive statistics, focusing on mean and percentage score improvements. The results of this community service project indicate that Partner's knowledge in processed chili products escalated from 45% to 95%, partners' skill in processing diverse chili products advanced from 40% to 90%, the ability to understand and design labels and food packaging enhanced from 35% to 85%, and understanding and abilities in financial management rose from 45% to 80%.